APLIKASI TEORI MYRA ESTRIN LEVINE DALAM PRAKTEK KEPERAWATAN - Euis Suhartini; Irna Nursanti (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Myra Estrin Levine's theory has a central role in guiding nursing practitioners in providing holistic care with a focus on understanding and meeting basic human needs. This study explores the application of this theory in nursing practice, highlighting the challenges of integrating the theory's principles into daily practice. Through a case study of a patient with a history of hypertensive disease and a kidney transplant, we demonstrate an attempt to apply the theory to formulate nursing diagnoses and design appropriate interventions. Although providing a solid foundation, the limitations of the theory, such as the focus on individualized disease and lack of support for health promotion, raise questions about the relevance and sustainability of application in diverse clinical contexts. Evaluation of an intervention based on Levine's conservation principles indicated improvements in thermoregulation and a decrease in patient anxiety. The conclusions highlight the need for further research to understand the application of this theory in a changing healthcare context, with in-depth reflection on the challenges and opportunities in applying its principles.